2021
DOI: 10.21123/bsj.2021.18.1.0102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bimetallic Au–Pt / TiO2 Catalysts as an Efficient Catalyst for the Photodegradation of Crystal Violet Dye

Abstract: Bimetallic Au –Pt catalysts supporting TiO2 were synthesised using two methods; sol immobilization and impregnation methods. The prepared catalyst underwent a thermal treatment process at 400◦ C, while the reduction reaction under the same condition was done and the obtained catalysts were identified with transmission electron microscopy (TEM) and energy-dispersive spectroscopy (EDS). It has been found that the prepared catalysts have a dimension around 2.5 nm and the particles have uniform orders leading to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…
10,11, and photodegradation [12][13][14] . It has been found that the photocatalytic degradation process is an interesting method because of its low cost, as well as because it
…”
mentioning
confidence: 99%
“…
10,11, and photodegradation [12][13][14] . It has been found that the photocatalytic degradation process is an interesting method because of its low cost, as well as because it
…”
mentioning
confidence: 99%